ความสัมพันธ์ของบุคลิกภาพที่มีต่อความฉลาดทางอารมณ์ ของบุคลากรทีมสุขภาพโรงพยาบาลอ่างทอง - วัลลภา กิตติมาสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
This research is a narrative research at a time has its objective to study relation between personality and emotional intelligence of healthy team personnels at Angthong Hospital As well as to study personnal data, mental health, personality and emotional intelligence of healthy team personnels at Angthong Hospital. The samplings are 365 healthy team personnel working at Angthong hospital at the time of data collecting. The instrument are personal questionnaire, mental health status screening test form, personality test, emotional intelligence evaluation form. Data are analyzed with percentage, mean, standard deviation. Relation to variation in analyzed with unpair t-test, ANOVA. Relation among mental health status, personality, emotional intelligence with Pearson’s Product. The result revealed that the samplings of 365 healthy team personnel at Angthong hospital mostly were female between 26-40 years of age, bechelor s degree education, marriage, with 1-10 year work experience, having working status of operator, extraversion personality is 28.22% stability personality is 25.34%, neuroticism personality is 24.66%, introversion personality is 21.78%. It is also found that emotional intelligence of health team personnels had average scores higher than regular average scores except in the group of 26-60 years old whose emotional intelligence of good work had average scores equal to regular average scores. Component of emotional intelligence of good work, motivation and relationship, component of emotional intelligence of happiness of life had average scores lower than regular average scores. Health team personnel of 18-25 years had positive related mental health in high level with emotional intelligence (R=.857) statistical significance p<0.01, sex, age, education, marital status, work experience. Type of work related to emotional intelligence of statistical significance p<0.05, extraversion personality had positive relation in high level (R=.655), neuroticism personalities had positive relation in medium level (R=.591) at statistical significance at p<0.01. Health team personnel of 26.60 years had positive related mental health in high level with emotional intelligence (R=.962) statistical significance p<0.01, sex, age, education, type of work had related to emotional intelligence statistical significance of p<0.05. Marital status and work experience related to emotional intelligence of statistical significance p<0.01. Extraversion personalies had positive relation in medium level (R=.475). Neuroticism personality medium level to emotional intelligence (R=.527) at statistical significance of p<0.01